2020
DOI: 10.1111/een.12836
|View full text |Cite
|
Sign up to set email alerts
|

The effects of host plant species on adult oviposition and larval performance of the aphid predator Aphidoletes aphidimyza

Abstract: 1. Although preference-performance relationships in insects are typically studied in a bi-trophic context, it is well known that host plants can affect both the preference and performance of natural enemies of herbivorous insects.2. This study presents evidence from field and laboratory studies that two species of milkweeds, the putatively less defended Asclepias incarnata and the putatively more defended Asclepias syriaca, differentially affect adult oviposition and larval performance in Aphidoletes aphidimyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Some aphid species can sequester secondary metabolites from their host plants and thus affect the survival and development of their natural enemies (Helms et al , 2004; Desneux et al , 2009; Erb and Robert, 2016; Mohl et al , 2020; Monticelli et al , 2021). To test this possibility, we evaluated the performance of Chr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some aphid species can sequester secondary metabolites from their host plants and thus affect the survival and development of their natural enemies (Helms et al , 2004; Desneux et al , 2009; Erb and Robert, 2016; Mohl et al , 2020; Monticelli et al , 2021). To test this possibility, we evaluated the performance of Chr.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, A. fabae and R. padi are considered a poor feeding resource to other aphid predators that have been termed 'generalists' such as coccinellid beetles (Rana et al, 2002;Toft, 2005). Some aphid species can sequester secondary metabolites from their host plants and thus affect the survival and development of their natural enemies (Helms et al, 2004;Desneux et al, 2009;Erb and Robert, 2016;Mohl et al, 2020;Monticelli et al, 2021). To test this possibility, we evaluated the performance of Chr.…”
Section: Survival and Consumption Ratesmentioning
confidence: 99%
“…(Hypocreales: Clavicipitaceae) and chooses to lay its eggs where the fungus is absent. Second, there may be differences in honeydew produced by different states of aphids Mohl et al (2020). found that honeydew quality directly affects the health of A. aphidimyza adults or has a repellent effect on their foraging behavior.…”
mentioning
confidence: 99%